DÉVELOPPEMENT DURABLE ET MODE : RÉFLEXIONS TERMINOLOGIQUES - Silvia CALVI (Studia Universitatis Babeş-Bolyai. Philologia, 2024)
Sustainable Development and Fashion: Terminology Considerations. Since the beginning of the 2000s, international and local initiatives to promote sustainable development in the fashion industry have been carried out. These actions contributed to the spread of a new terminology introduced in several types of texts – from institutional documents to e-commerce articles and texts from the specialised press. The aim of this study is to explore this terminology in a corpus built ad hoc. Firstly, the analysis of the most frequent terms and collocations will lead to the description of sustainable fashion subdomains, to underline the interdisciplinarity of this sector; secondly, the focus will be on the formation of terms and collocations.